Pengaruh Latihan Five Dot Drill Terhadap Peningkatan Kelincahan - Dwitama, Rizki Septa putra; Sutisna, Nana; Rohendi, Andang; Rustiawan, Hendra (Jurnal Keolahragaan, 2024)
This research aims to determine whether there are positive changes in body agility as a result of the five dot drill treatment. The research method used is pre-experimental design. The research location is at SMK YPS 1 Ciamis Regency. The research subjects were 20 people. The sampling technique is total sampling. Based on data analysis using SPSS series 24, the results of data processing were, "The five dot drill exercise had a significant influence on increasing agility in male students at YPS Vocational School, Ciamis Regency." Conclusion: Five dot drill training has a significant effect on increasing agility. Suggestion: It is hoped that similar research will be carried out so that the repertoire of physical condition elements of agility will further develop. Penelitian ini bertujuan untuk mengetahui adanya perubahan seara positif pada kelincahan tubuh dari hasil perlakuan five dot drill. Metode penelitian yang digunakan adalah pre-experimental design. Lokasi penelitian di SMK YPS 1 Kabupaten Ciamis. Subjek penelitian berjumlah 20 orang. Teknik pengambilan sampel yaitu total sampling. Berdasarkan analisis data menggunakan SPSS serie 24, hasil pengolahan data adalah, “Latihan five dot drill memberikan pengaruh yang signifikan terhadap peningkatan kelincahan pada siswa putra SMK YPS Kabupaten Ciamis.” Kesimpulan: Latihan five dot drill berpengaruh secara signifikan terhadap peningkatan kelincahan. Saran: Diharapkan adanya penelitian yang sejenis agar khasanah unsur kondisi fisik kelincahan semakin berkembang.